Racial Resentment, Empathy, and Support for Release during COVID-19: Results from a Survey Experiment - Stefan Ivanov; Meghan A. Novisky; Matt Vogel (Socius, 2021)
Coronavirus disease 2019 (COVID-19) has presented the American criminal justice system with unprecedented challenges, including protecting the safety of incarcerated men and women. Given the ill-suited structure of correctional facilities to facilitate health and safety guidelines, one solution is decarceration. Yet decarceration has faced political and public backlash. As no evidence currently exists on how the public views this emergency solution, the authors examined the correlates of support for decarceration by conducting a survey experiment in which respondents were randomly presented with information on the dangers of COVID-19 in prisons and jails. Respondents’ attitudes toward releasing various subgroups of the incarcerated population were then measured. The findings indicate that learning about the health risks of COVID-19 in correctional facilities had no discernable effect on support for decarceration for any subgroup. Racial resentment consistently predicted opposition to release for all groups, although its effect largely operated through empathetic identification with those who commit crimes.